Permanent maxillary first molar with three mesiobuccal canals - Rohit Nair; Sandhya Khasnis; Jayaprakash D Patil (Wolters Kluwer Medknow Publications, 2019)
It is mandatory for every clinician to have a thorough knowledge about the normal internal anatomy of teeth; equally important is the awareness about variations in internal anatomy that could be seen with different teeth. The outcome of a root canal therapy depends significantly on the clinician's awareness about root canal anatomy, followed by their clinical skills. Literature states that the permanent maxillary first molar shows a wide variation in the number of canals particularly with respect to the mesiobuccal root. This case report describes the endodontic management of a permanent maxillary first molar with three distinct mesiobuccal canals.